TECHNOPHOBIA AS A CULTURAL AND PSYCHOLOGICAL PHENOMENON: Theoretical Analysis - Nestik, Timofey; Zhuravlev, Anatoly; Eduard, Patrakov; Marianna, Szabó Csilla; Lioudmila, Bautorina; Piurcosky, Fabricio Pelloso; Ferreira, Jeferson Vinhas (Interação - Revista de Ensino, Pesquisa e Extensão, 2019)
Today we can talk about a sufficient formation of both negative and positive attitudes towards the introduction of new technologies. This is the technophobia that continued to be fueled by such objective factors as job slashing caused by events and new inventions. Technophobia includes cognitive, emotional and behavioral components. Along with individual factors (self-efficacy, open-mindedness, anxiety level, user’s experience, emotional state, etc.), the formation of technophobia is influenced by interpersonal factors (communication with colleagues, friends and relatives on the subject of technologies), group and intergroup factors (clash of interests of different relevant groups in connection with the appearance of new technologies, group stereotypes – representations of typical users of the given technology, its developers, etc.), as well as societal factors (mass culture and mass media, the level of technological and economic development of a country, cross-cultural features). In this way, this is an increasingly important phenomenon, since the speed of innovation is very high. Thus, the purpose of this study is to present a theoretical analysis on this subject and to highlight the importance of conducting other research on this subject.